An algorithm for indoor SARS-CoV-2 transmission - Daniel Maxin; Spencer Gannon (Journal of Mind and Medical Sciences)
We propose a computer modeling approach for SARS-CoV-2 transmission that can be preferable to a purely mathematical framework. It is illustrated its functionality in a specific case of indoor transmission. Based on literature, we assume that infection is due to aerosols with viral particles that persist and accumulate for hours in the air even after the persons who produced them left the space. We incorporate also restricted opening hours as a mitigation measure and one possible behavioral change in response to this measure. It is shown via several examples how this algorithmic modeling approach can be used to run various scenarios in order to predict the efficacy of the intervention.